EFEKTIVITAS PENERAPAN MEDIA FLASHCARD UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS II SDN 065853 MEDAN DENAI - Yunita Sari Sinaga; Ismail Saleh Nasution (STKIP Subang, 2024)
The purpose of this study is to determine how effective the use of flash cards as a learning tool is to improve students' reading ability in grade II of SDN 065853 Medan Denai. This study uses quantitative and qualitative methods. In each cycle, observation sheets and tests are given to students to find out the results. This Classroom Action Research (PTK) is carried out in two cycles and involves various steps, such as planning, implementation, observation, and reflection. This study found that the use of flashcard learning media during the learning process improved the reading ability of grade II students. In addition, students are more interested in participating in the learning process in the classroom. The results showed that the percentage of student success increased from 42.9% in the first cycle to 90.48% in the second cycle. Therefore, it can be concluded that improving students' reading ability in grade II elementary school with flashcards can be an effective learning strategy.